Seismic performance of scaled IBS block column for static nonlinear monotonic pushover experimental analysis - Yip, C. C. (Penerbit UTM Press, 2018)
his paper presents the seismic performance of the down scaled 1:5 model IBS block column with non-linear static analysis. The aim of this research is to access the ultimate capacity and structural behaviour of the IBS block column. This paper demonstrates the theoretical prediction of the full-scale prototype strength based on scaling factors at non-linear state. Besides, this research investigates the ultimate shear capacity, stiffness, bolt strength, inter-storey drift and block separation for prediction of seismic performance levels. Concrete material properties, mix specification and steel reinforcement detailing for scaled model are tabulated in this paper. The methodology of this research begins with full scale prototype design, scaling to the small model and followed by the scaled model fabrication. Theoretical lateral load prediction associated with scaling factors are also performed. The experiment test was carried out on the assembled scaled 1:5 IBS block column with proper displacement measuring equipment on test rig and graphical capture tools. The data of roof top displacement with base shear capacity, inter-storey drift and gap separations were tabulated for discussions. The tested ultimate roof top displacement was 128 mm with 3.1 kN base shear. The calculated elastic stiffness of the IBS block column was 0.137 kN/mm, followed by yielding stiffness of 0.033 kN/mm and 0.014 kN/mm plastic stiffness. The significant inter-storey drift was due to cracking and crushing of column blocks edges. The measured maximum separation gap was 24.4 mm located at 340 mm height due to the rocking of the column. Based on seismic performance levels indicator from FEMA 273 & 356, the column was in the state of immediate occupancy with 21 mm roof top displacement and 1.7 kN base shear. The life safety is limited at 65.27 mm roof top displacement with 2.4 kN of base shear. All scaled down data was then reverted to full scale prototype capacity according with the respective scaling factors. It concluded that the IBS blockwork column is capable of resisting the seismic event without falling of the blocks that endanger the occupant life at the maximum credible earthquakes of 1.3 g horizontal spectral acceleration equivalent to X+ Mercalli’s scale.